Motion artifacts assessment and correction using optical tracking in synchrotron radiation breast CT. Issue 9 (29th July 2021) - Brombal, Luca; Arana Peña, Lucia Mariel; Arfelli, Fulvia; Longo, Renata; Brun, Francesco; Contillo, Adriano; Di Lillo, Francesca; Tromba, Giuliana; Di Trapani, Vittorio; Donato, Sandro; Menk, Ralf Hendrik; Rigon, Luigi
Abstract: Purpose: The SYRMA‐3D collaboration is setting up a breast computed tomography (bCT) clinical program at the Elettra synchrotron radiation facility in Trieste, Italy. Unlike the few dedicated scanners available at hospitals, synchrotron radiation bCT requires the patient's rotation, which in turn implies a long scan duration (from tens of seconds to few minutes). At the same time, it allows the achievement of high spatial resolution. These features make synchrotron radiation bCT prone to motion artifacts. This article aims at assessing and compensating for motion artifacts through an optical tracking approach. Methods: In this study, patients' movements due to breathing have been first assessed on seven volunteers and then simulated during the CT scans of a breast phantom and a surgical specimen, by adding a periodic oscillatory motion (constant speed, 1 mm amplitude, 12 cycles/minute). CT scans were carried out at 28 keV with a mean glandular dose of 5 mGy. Motion artifacts were evaluated and a correction algorithm based on the optical tracking of fiducial marks was introduced. A quantitative analysis based on the structural similarity (SSIM) index and the normalized mean square error (nMSE) was performed on the reconstructed CT images. Results: CT images reconstructed through the optical tracking procedure were found to be as good as the motionless reference image. Moreover, the analysis of SSIM and nMSE demonstrated that an uncorrected motion of the order of the system's point spread function (around 0.1 mm in the present case) can be tolerated. Conclusions: Results suggest that a motion correction procedure based on an optical tracking system would be beneficial in synchrotron radiation bCT.